Analysis of Vegetation Structure and Sustainable Management of Mangrove Forests - Jelibseda; Eni kamal; Abdul Razak; Skunda Diliarosta (Jurnal Penelitian Pendidikan IPA, 2024)
The objective of this study is to examine the structure of mangrove vegetation on Dompak Island and develop sustainable management strategies. The research employs a descriptive approach with purposive sampling as the sampling technique. Research instruments include a hygrometer, raffia rope, location map, hand refractometer, roll meter, hand counter, and identification book. Additional materials used are tissue, an oven, GPS, 70% alcohol, rope, plastic bags, analytical scales, a camera, distilled water, aluminum foil, a multi-tester, mangrove data, and a refractometer. The study identified six mangrove species on Dompak Island: Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, and Ceriops tagal. Among these, Rhizophora apiculata was the most abundant, with 68 individuals at the tree level, 18 at the sapling level, and 19 at the seedling level. Based on SWOT analysis, the recommended strategy for managing Dompak Island’s mangroves is conservation-focused. This includes protecting the ecosystem, prohibiting destructive activities such as deforestation, and implementing regulations for local communities to ensure the sustainability of mangrove forests. In conclusion, the mangrove vegetation structure on Dompak Island, Tanjungpinang City, remains diverse and well-preserved.